Profile of isokinetic eccentric-to-concentric strength ratios of shoulder rotator muscles in elite female team handball players - dos Santos Andrade, M.; Fleury, A. M.; Barbosia de Lira, C. A.; Dubas, J. P.; da Silva, A. C. (Journal of Sports Sciences, 2010)
The purpose of this study was to establish the isokinetic profile of shoulder rotator muscles strength in female handball players. Twenty-seven handball players performed concentric and eccentric strength tests of both dominant and non-dominant upper limbs on an isokinetic dynamometer. Internal and external rotator muscles peak torque was assessed at 1.05, 3.14, and 5.23 rad/s in concentric mode and at 3.14 and 5.23 rad/s in eccentric mode. Concentric balance ratio and functional ratio were obtained. Bi-lateral deficiency was compared. Concentric strength for internal and external rotation was significantly greater for the dominant than for the non-dominant limb for all speeds (P = 0.0001). For eccentric actions, internal rotator muscles were stronger in the dominant than the non-dominant limb (P = 0.0001) at both speeds. Concentric balance and functional balance ratios did not differ between sides at 3.14 rad · s-1 (P = 0.1631), but at 5.23 rad/s the functional balance ratio in the dominant limb was lower than for the non-dominant limb (P = 0.0500). Although the dominant side was stronger than the non-dominant side, balance concentric ratios remained the same, with only the functional strength ratio different at 5.23 rad/s. Our results suggest that concentric strength exercises be used for internal and external rotators on the non-dominant side, and functional exercise that improves eccentric rotation strength for prevention programmes.